Uji Antagonis Pseudomonas sp. Asal Endofit Perakaran Padi Terhadap Penyakit Blas (Pyricularia oryzae) Secara In Vitro - Andree Saylendra; Tubagus Bahtiar Rusbana; Linda Herdiani (Faculty of Agriculture, Pattimura University, 2015)
The purpose of this research was to determine the antagonistic bacteria Pseudomonas spp. of paddy roots endophytic against disease blast (Pycularia oryzae) in vitro. This research was conducted at the Laboratory of Agroecology, Faculty of Agriculture, University of Sultan Ageng Tirtayasa on April to June 2015. This research implemented experimental one factor that arranged in Completely Randomized Design with three replications. The treatment consisted of 9 isolates of Pseudomonas sp. which was screened from endophytic roots of paddy plants. The test results showed that antagonistic in vitro testing could inhibit the growth P. oryzae. Inhibition of 9 isolates to the growth Pseudomonas spp. had the significant clear zone. Isolate Ps 17 (58.89%), Ps 22 (54.44%), Ps 37 (52.06%) and Ps 39 (61.42%) have the largest inhibition. The results showed that the bacteria Pseudomonas sp. on this research is potential on controlling disease blast in paddy plant.